DeFi - Kim, Seoyoung (--For dummies., 2023)
The promise of decentralized finance (DeFi for those up on their financial lingo) as a disruptor to financial institutions makes it must-know for anyone involved in finance. DeFi For Dummies provides an easy-to-understand option for unraveling the past, present, and future of DeFi. Understand current DeFi applications, including how to build basic applications on the leading platforms, and get a look into the future’s most promising new DeFi solutions. Staying ahead of the game is critical for finance professionals these days, and this Dummies guide makes it possible, with full coverage of how DeFi affects asset management, lending and borrowing, and investment markets. Wrap your mind around DeFi and start getting hands on, the Dummies way.